HUBUNGAN KESIAPAN BELAJAR MANDIRI TERHADAP NILAI BLOK PERTAMA PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA TAHUN AJARAN 2018/2019 - RIMA RAHMI; DESI ISNAYANTI (LP2MTBM MAKARIOZ, 2021)
Problem based learning (PBL) approach is aiming at increasing the self directed learning ability that can be supported by theself-directed learning readiness (SDLR). Self directed learning readiness (SDLR) is the someone’s readiness to do learningprocess that initiated by himself, with or without others help. The level of SDLR can affect and estimate someone’s learningsuccess. The higher the level of SDLR, then the higher the learning achievement of someone can get. This study aimed toknow the correlation of self-directed learning readiness towards first block score of the college students at Medical FacultyMuhammadiyah University of North Sumatera academic year 2018/2019. This study was a descriptive analitic study withcross sectional design. The samples of this study were 129 first year college students of FK UMSU academic year2018/2019 that were taken with total sampling technique. Most college students have high SDLR score with 97 students, andthen followed by moderate SDLR score with 32 students (24,8%), and no student with low SDLR score (0%). From the blockfinal exam score, most students got pass achievement with total 55 students (42,6%), and then followed by borderlineachievement with 50 students (38,8%), not pass achievement with 22 students (17,1%) and superior achievement with 2students (1,7%). The results of this study were tested with the Kruskal-Wallis test. From the Kruskal-Wallis test it’s obtainedthat the P Value is 0.568 . It means that there is no correlation of self-directed learning readiness towards first block score.The self-directed learning readiness has no relation with the first block score of college students at Medical FacultyMuhammadiyah University of North Sumatera academic year 2018/2019.